Akibat Hukum Tindakan Anarkis Demonstran Terhadap Perusakan Fasilitas Umum dan Penyerangan Petugas Kepolisian (Studi Kasus Penolakan Pengesahan UU Nomor 11 Tahun 2020 Tentang Cipta Kerja) - Ida Ayu Sri Intan Dwiyanti; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Fakultas Hukum Universitas Warmadewa, 2021)
The aim of this study is to find out law enforcement for demonstrators, especially in demonstration activities against Law Number 11 of 2020 Cipta Kerja, which was passed on October 5, 2020 and the legal consequences of attacks by police officers in their task of securing demonstrations. Demonstration is a form of democracy recognized by the government of the Republic of Indonesia based on the 1945 Constitution. By normative research methods several comparisons can be drawn with other laws relating to demonstration activities. The results of this study concluded that the demonstration activity began peacefully and ended in chaos and the police had the authority to secure the demonstrators so that the situation was under control, but the two sides turned into physical conflict. Other research results, in-depth studies are still needed on good demonstration procedures without harming the authorities.